The Effect of KUR and BLT Programs on MSME Performance with Differentiation Strategy as A Mediation Variable - Kardi, Kardi; Hutahuruk, Marice Br; Handoyo, Leonardus Teguh (First Ciera Publisher, 2024)
This study aims to examine the impact of the People's Business Credit (KUR) and Direct Cash Assistance (BLT) programs on MSME performance through differentiation strategy mediation. This study involved MSME actors in Salatiga City using a purposive sampling method to determine the sample. Data were processed using Partial Least Square- Structural Equation Modeling (PLS-SEM). The reported findings are that the KUR and BLT programs have a significant positive effect on differentiation strategies and also on MSME performance. It is also proven that differentiation strategies mediate the effect of KUR and BLT programs on MSME performance. This can be a reference for MSME actors to increase their business capital by using the KUR and/or BLT programs wisely to support the implementation of differentiation strategies to improve their business performance.